NOTES ON THE DISTRIBUTIONS AND TAXONOMY OF TWO SPECIES OF FRESHWATER CRABS OF THE GENUS ISOLAPOTAMON BOTT, 1968 (DECAPODA, BRACHYURA, POTAMIDAE) FROM SARAWAK, MALAYSIA - Das, Indraneil; Jongkar, Grinang; Ng, Peter K. L. (Brill Publishing, 2014)
Of the seven species of potamid freshwater crabs of the genus Isolapotamon Bott, 1968, known from Sarawak, the type localities of two species, I. borneense Ng & Tan, 1998, and I. grusophallus Ng & Yang, 1986, are not known with accuracy. Through extensive collections in Sarawak, the provenances of these localities are now determined. Isolapotamon borneense is found in the upper parts of the Baram River in northern Sarawak; while I. grusophallus occurs in Gunung Penrissen and adjacent areas in central Sarawak. The taxonomy of these two species is also discussed.